(untitled) (Bangladesh Journal of Medical Science, 2020)
Purpose: For making denture in maxillectomy cases is very difficult and challenging to get the retention tomake the denture stable in its position during functioning. This case report describes a clinical condition inwhich patient was treated with a maxillary obturator with zygomatic suspension wiring due to insufficientretention in the palate. Materials and Methods: A 63-year-old patient had gone to a subtotal maxillectomybecause following myofibroblastic sarcoma andwas issued with bilateral circum-zygomatic wiring hooksimmediately after surgery. The patient had less than a third of their alveolar ridge remaining and did notprovide sufficient retention on its own. The wires were used for the retention because natural retentioncould not get due to inadequate maxillary ridge. While the denture was being fabricated, a temporaryfeeding plate was provisioned to the patient. Counter hooks were implemented on the definitive upperdenture, posterior to molars, to attach to the zygomatic suspension hook. Final upper denture was furtherreinforced with denture adhesive on it. A lower denture was also fabricated for the said case followingconventional protocols of jaw relation determination. Results: The obturator provided with adequate sealand leak proof phonetics. The zygomatic wiring coupled with denture adhesive were sufficient to provideadequate retention. Conclusion: Zygomatic suspension wires coupled with counter hooked obturatorprosthesis provide rehabilitation of patients with palatal defects with inadequate maxillary arch forretention.However long-term repeated use of such wires might expose the patient to secondary infectionsand should be kept in consideration Clinical Significance: Circum-zygomatic suspension wiring providesufficient retention to sustain the upper obturator prosthesis in place. However, the retention was stillinadequate, so denture adhesives were used to make it more stable. Bangladesh Journal of Medical Science Vol.19(3) 2020 p.582-585